Semi-subsistence farms in Portugal - Dos-Santos, M.J.P.L.; Barreiro, R.P.; Pereira, J.M.T.; Ferreira da Silva, A (Journal of Agricultural Economics and Development, 2014)
This paper aims to analyze the farm structure in Portugal, the main reasons that explain the duality of the agrarian system between the Southern and Northern regions of the country, and the potential consequences on agricultural development. Besides the farm structure in Portugal as a recurrent issue on the Portuguese literature, the concept of semi-subsistence farms in Portugal was never recognized. This paper tries to overcome this gap on the literature. The methodology used was a univariate statistical analysis, due to the inexistence of more strong information and data. The results confirm the contribution of subsistence farming to household incomes, and social and rural development, with strong development potential due to the macroeconomic situation in Portugal. But concerning that, stronger quantitative analysis and studies are needed. The conclusions suggest that the EU Common Agricultural Policy instruments best suited the response to the specific needs of these subsistence farmers due to the prevalence and importance of small farms in Portugal.